2015
DOI: 10.1155/2015/279814
|View full text |Cite
|
Sign up to set email alerts
|

Histology and Morphology of the Brain Subarachnoid Trabeculae

Abstract: The interface between the brain and the skull consists of three fibrous tissue layers, dura mater, arachnoid, and pia mater, known as the meninges, and strands of collagen tissues connecting the arachnoid to the pia mater, known as trabeculae. The space between the arachnoid and the pia mater is filled with cerebrospinal fluid which stabilizes the shape and position of the brain during head movements or impacts. The histology and architecture of the subarachnoid space trabeculae in the brain are not well estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 17 publications
2
50
0
3
Order By: Relevance
“…Interestingly, a microscopic examination of the brain-meningioma interface revealed proliferation of hyperplastic arachnoid trabeculae, (below the arachnoid membrane at the brainmeningioma interface) in the meningioma with a thin connective capsule (shown in Fig 1A of the study) [7]. After the study, it was reported that the arachnoid trabeculae and granulations are composed of type 1 collagen [18]. The arachnoid is composed of two layers.…”
Section: Fig 2 Comparisons Of Age Mean Frontal Skull Hu Value Gtv mentioning
confidence: 77%
“…Interestingly, a microscopic examination of the brain-meningioma interface revealed proliferation of hyperplastic arachnoid trabeculae, (below the arachnoid membrane at the brainmeningioma interface) in the meningioma with a thin connective capsule (shown in Fig 1A of the study) [7]. After the study, it was reported that the arachnoid trabeculae and granulations are composed of type 1 collagen [18]. The arachnoid is composed of two layers.…”
Section: Fig 2 Comparisons Of Age Mean Frontal Skull Hu Value Gtv mentioning
confidence: 77%
“…SAT consisted of pillars, columns, sheets, branched fibrils, and other complex structures with fibril diameters that varied from 0.5-3 µm [3]. Optical coherence tomography was utilized to show that SAT fiber diameter varies from 19.2-45.5 µm [27].…”
Section: Structural Morphologymentioning
confidence: 99%
“…4 Rekomendasi Health Technology Assessment dan Departemen Kesehatan Republik Indonesia terhadap semua bayi yang baru lahir harus mendapatkan profilaksis 1 mg vitamin K1 dosis tunggal intramuskular. 3,5 Angka kejadian APCD pada neonatus yang tidak mendapatkan profilaksis vitamin K berkisar 1 tiap 200-400 orang. 6 Insidensi APCD onset lambat pada bayi yang mendapatkan profilaksis vitamin K1 secara oral adalah 1,4-6,4 per-100.000 sedangkan secara intramuskular 0,25-3,2 per-100.000.…”
Section: Laporan Kasus Tertia Dkk 2018unclassified